Damage accumulation during high temperature fatigue of Ti/SiCf metal matrix composites under different stress amplitudes. (July 2021) - Wang, Ying; Xu, Xu; Zhao, Wenxia; Li, Nan; McDonald, Samuel A.; Chai, Yuan; Atkinson, Michael; Dobson, Katherine J.; Michalik, Stefan; Fan, Yingwei; Withers, Philip J.; Zhou, Xiaorong; et al.
Abstract: The damage mechanisms and load redistribution taking place under high temperature (350 °C), high cycle fatigue (HCF) of TC17 titanium alloy/unidirectional SiC fibre composites have been investigated in situ using synchrotron X-ray computed tomography (CT) and X-ray diffraction (XRD) under two stress amplitudes. The three-dimensional morphology of the fatigue crack and fibre fractures has been mapped by CT. At low stress amplitude, stable growth occurs with the matrix crack deflecting by 50-100 µm in height as it bypasses the bridging fibres. At higher stress amplitude, loading to the peak stress led to a burst of fibre fractures giving rise to rapid crack growth. Many of the fibre fractures occurred 50-300 µm above/below the matrix crack plane during rapid growth, contrary to that in the stable growth stage, leading to extensive fibre pull-out on the fracture surface. The changes in fibre loading, interfacial stress, and the extent of fibre-matrix debonding in the vicinity of the crack have been mapped over the fatigue cycle and after the rapid crack growth by XRD. The fibre/matrix interfacial sliding extends up to 600 µm (in the stable-growth zone) or 700 µm (in the rapid-growth zone) either side of the crack plane. The direction of interfacial shear stress reverses over the loading cycle, with the maximum frictional sliding stress reaching ~55 MPa in both regimes. In accordance with previous studies, it is possible that a degradation in fibre strength at elevated temperature is responsible for bursts of fibre fracture and rapid crack growth under higher stress amplitude. Graphical abstract: Image, graphical abstract